Flipping activity in Malaysian IPO market: a new explanation from the winners' curse perspective. (25th July 2019) - Che-Yahya, Norliza; Abdul-Rahim, Ruzita; Mohd-Rashid, Rasidah
This study examines the influence of winners' curse phenomenon on flipping activity through a winners' curse measurement proposed in Amihud et al. (2003). The study defines winners' curse using allocation rate ( ALLOCj ) which is as the natural log of the reciprocal of investor demand or oversubscription ratio. In a view, the presence of winners' curse in an IPO market leads to high flipping activities indicating that new IPO subscribers are not willing to retain the allocated IPOs for longer term. However, from another view where high ALLOCj could also reflect IPOs with low demand, the immediate trading activity by the new subscribers is not possible to be done. The latter view suggests that ALLOCj should produce low flipping activities. Using a sample of 381 IPOs issued in Bursa Malaysia from January 2000 to December 2013, the cross-sectional multiple regression analyses results report that ALLOCj relate significantly and negatively to flipping activity. The significant relationship supports the latter view that uninformed investors are more likely to win big IPOs which are not demanded by the informed investors. Therefore, the lower demanded IPOs produce low flipping activities.